Hubungan Koordinasi Mata Tangan dan Stabilitas Bahu terhadap Akurasi Memanah Di Kota Denpasar - I Kadek Pradnya Deva; Ni Luh Nopi Andayani; I Gusti Ayu Artini; Ari Wibawa (Universitas Pahlawan Tuanku Tambusai, 2026)
Archery is a precision sport that requires high levels of accuracy, consistency, and movement control. Archery accuracy is influenced by physical and neuromuscular components, including hand-eye coordination and shoulder stability. This study aimed to determine the relationship between hand-eye coordination and shoulder stability with archery accuracy among archery athletes in Denpasar City. This study used an observational analytic design with a cross-sectional approach. The subjects were 55 archery athletes selected using purposive sampling based on inclusion and exclusion criteria. Archery accuracy was measured using a standard target scoring system at a distance of 30 meters, hand-eye coordination was measured using the Alternate Hand Wall Toss Test, and shoulder stability was measured using the Upper-Quarter Y-Balance Test on the bow-arm and draw-arm shoulders. Data were analyzed using Spearman rho. The results showed a positive and significant relationship between hand-eye coordination and archery accuracy (r = 0.348; p = 0.009). Bow-arm shoulder stability was also significantly related to archery accuracy (r = 0.556; p = 0.000), as was draw-arm shoulder stability (r = 0.516; p = 0.000). This study concludes that hand-eye coordination and shoulder stability are significantly related to archery accuracy among archery athletes in Denpasar City.